2012
DOI: 10.4103/2230-973x.100039
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of jackfruit mucilage and its comparative evaluation as a mucoadhesive and controlled release component in buccal tablets

Abstract: Background:The purpose of the present research work was to extract jackfruit mucilage, use it as a mucoadhesive agent, and to develop extended release buccoadhesive tablets with an intention to avoid hepatic first-pass metabolism, by enhancing residence time in the buccal cavity.Materials and Methods:The mucilage was isolated from the jackfruit pulp by the aqueous extraction method and characterized for various physiochemical parameters as well as for its adhesive properties. Three batches of tablets were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However the amylase content of JFSS (∼24-32%) is comparable with potato starch. It is already established as tablet binder, suspending agent and emulsifier [33]. Moreover, JFSS was already investigated as mucoadhesive agents in the development of controlled release drug delivery [33][34][35].…”
Section: Q2mentioning
confidence: 99%
“…However the amylase content of JFSS (∼24-32%) is comparable with potato starch. It is already established as tablet binder, suspending agent and emulsifier [33]. Moreover, JFSS was already investigated as mucoadhesive agents in the development of controlled release drug delivery [33][34][35].…”
Section: Q2mentioning
confidence: 99%
“…JM has been reported to contain polysaccharides, lignins, and isoflavones in different amounts, which possess properties, such as anti‐cancer, anti‐oxidant, and anti‐ulcer. [ 14‐15 ] Polysaccharides provide a positive environment for cell growth whereas lignins affect cell viability through a reduction in cell proliferation, rather than by inducing cytotoxic death, especially at high concentrations and long treatment times. [ 44 ] Isoflavones have been reported to strongly inhibit the cell growth of stomach cancer cell lines in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Their health benefits are wide ranging from anticancer to antihypertensive, antiaging, antioxidant, and anti‐ulcer. [ 14, 15 ] The potential use of jackfruit mucilage has been explored in pharmaceutical applications as tablet binders, excipients, and in drug delivery as it has a good swelling index of 12.66 and a good water uptake capacity. [ 9, 16 ] Even though there are studies that have reported the use of plant‐based gums blended with PCL [ 11, 17‐21 ] as a potential to be used as biomedical applications, from our literature survey it was found that there is no reported work on blends of jackfruit mucilage with polymers targeted toward tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Mucilages are physiological products and form slimy masses (Jani et al, 2009). Structurally, the extrusion of mucilage subsequent to exposure of dry seed to an aqueous environment is the result of the hydration and expansion of the mucilage, the rupture of the radial fragment of the primary cell wall, and the subsequent formation of a gel (Sabale et al, 2012;Teixeira et al, 2010); the same definition is ''loab'' in traditional medicine. Some of these ''loab plants'' such as Ispaghula (Plantago ovate Forsk), Quince (Cydonia oblonga Miller) seed, and marshmallow (Althaea officinalis Linn) had been used most of the time in traditional manuscript and ancient Persian scholars administered them via simple or in compound with other plants for treatment of a variety of diseases, so in this study, a more extensive discussion of these plants is explained.…”
Section: Resultsmentioning
confidence: 99%
“…In current medicine, mucilage as a production of many various plant species (Deng et al, 2012), regularly used adjuvant in pharmaceutical preparations (Sabale et al, 2012) and contains sugar and uronic acid units (Sabale et al, 2012). Plant mucilages have evoked much interest due to their various applications in pharmacy.…”
Section: Introductionmentioning
confidence: 99%